Effectiveness of Toothpastes on SARS-CoV-2 Viral Load in Saliva - Fernanda P Eduardo; Luciana Corrêa; Fernanda Mansur; Carlos Benitez; Nelson Hamerschlak; João Renato Rebello Pinho; Debora Heller; Letícia Mello Bezinelli (Elsevier, 2022)
ABSTRACT: Introduction: The effect of toothpastes on viruses, such as SARS-CoV-2, is unknown. This study investigated the short-term effect of toothpastes containing antimicrobial properties in patients with novel coronavirus disease 2019 (COVID-19) to determine whether they could reduce the SARS-CoV-2 salivary viral load. Methods: Hospitalised patients with COVID-19 (n = 83) were instructed to perform toothbrushing with 1 of 3 arms: a toothpaste containing 0.96% zinc (zinc oxide, zinc citrate) in a silica base (Test 1), a toothpaste containing 0.454% SnF2 in a silica base (Test 2), and a nonantibacterial toothpaste (control). Saliva was collected before intervention (T0), immediately after intervention (T1), and 30 (T2) and 60 minutes (T3) after intervention. The SARS-CoV-2 salivary viral load was measured using quantitative real-time polymerase chain reaction (qRT-PCR) assays. For Test 1 and Test 2 toothpastes, the fold reductions were normalised to baseline and to the control toothpaste at each time point after brushing. A fold change of ≥2 is considered clinically effective. Results: Brushing with the Test 1 toothpaste reduced the SARS-CoV-2 salivary viral load by 4.06-fold at T1, by 2.36-fold at T2, and by 1.42-fold at T3. Similarly, brushing with a Test 2 toothpaste reduced the SARS-CoV-2 salivary viral load by 2.33-fold at T1, by 2.38-fold at T2, and by 0.77-fold at T3. Conclusions: Immediately after brushing, the use of antimicrobial toothpastes reduced the salivary viral load of patients with COVID-19. The trial was registered on https://clinicaltrials.gov/ (NCT04537962).